Enhanced flotation of high density polyethylene and polyvinyl chloride mixtures based on clean corona modification - Wang, Yinan; Zhao, Yue; Guo, Linyi; Han, Fengrong; Li, Xiaofeng (Elsevier Ltd, 2022)
The dramatic increase in waste plastics has caused harm to both human health and the environment. Due to the variety of plastic products and their complex components, it is a technical challenge to effectively separate them. High density polyethylene (HDPE) and polyvinyl chloride (PVC) both have a high detection frequency in the common solid waste streams like automobile shredder residue (ASR), and due to the similar properties of different plastics, their mixtures lack reliable separation methods. Specifically for this kind of mixtures, this work provided a novel separation strategy with prepositive corona modification and postpositive flotation units. To obtain the optimal separation parameters, flotation performance of HDPE and PVC were investigated under different modification conditions controlled by the corona polarity, discharge power and exposure time. Besides, the modification mechanism was revealed through multi-characterization tests on surface morphology, molecular weight, contact angle, and spectrums. The results showed that corona discharge can generate non-thermal plasma to activate the surfaces of HDPE and PVC, thereby increasing their floatability difference. Under the optimal conditions of 300 W positive discharge power and 8000 ms exposure time, HDPE turned into the sinking tail while PVC still accumulated in the floating product, leading to the maximum separation recovery and purity of 96.36% and 97.01%, respectively. Amorphous low-molecular weight oxidic substances emerged on the upper layer of polymers was verified by the multi-characterization, representing in varying degrees of oxidation and chain scission (HDPE > PVC). Since the corona modification is reagent-free-addition and rapid in-line process, this work showed great advantages in the total cost of separation (only 450.03 USD/t) and potential environmental benefits, which also paves a clean way for the recycling of HDPE and PVC.